Nonalcoholic Fatty Liver Disease: Pathogenesis and Therapeutics from a Mitochondria-Centric Perspective - Aaron M. Gusdon (Oxidative Medicine and Cellular Longevity, 2014)
Nonalcoholic fatty liver disease (NAFLD) describes a spectrum of disorders characterized by the accumulation of triglycerides within the liver. The global prevalence of NAFLD has been increasing as the obesity epidemic shows no sign of relenting. Mitochondria play a central role in hepatic lipid metabolism and also are affected by upstream signaling pathways involved in hepatic metabolism. This review will focus on the role of mitochondria in the pathophysiology of NAFLD and touch on some of the therapeutic approaches targeting mitochondria as well as metabolically important signaling pathways. Mitochondria are able to adapt to lipid accumulation in hepatocytes by increasing rates of beta-oxidation; however increased substrate delivery to the mitochondrial electron transport chain (ETC) leads to increased reactive oxygen species (ROS) production and eventually ETC dysfunction. Decreased ETC function combined with increased rates of fatty acid beta-oxidation leads to the accumulation of incomplete products of beta-oxidation, which combined with increased levels of ROS contribute to insulin resistance. Several related signaling pathways, nuclear receptors, and transcription factors also regulate hepatic lipid metabolism, many of which are redox sensitive and regulated by ROS.